Genome-wide methylation and transcriptome analysis in penile carcinoma: uncovering new molecular markers - Kuasne, Hellen; Syllos Colus, Ilce Mara de; Busso, Ariane Fidelis; Hernandez-Vargas, Hector; Barros-Filho, Mateus Camargo; Marchi, Fabio Albuquerque; Scapulatempo-Neto, Cristovam; Faria, Eliney Ferreira; Lopes, Ademar; Guimaraes, Gustavo Cardoso; Herceg, Zdenko; Rogatto, Silvia Regina [UNESP] (Biomed Central Ltd, 2015)
Background: Despite penile carcinoma (PeCa) being a relatively rare neoplasm, it remains an important public health issue for poor and developing countries. Contrary to most tumors, limited data are available for markers that are capable of assisting in diagnosis, prognosis, and treatment of PeCa. We aimed to identify molecular markers for PeCa by evaluating their epigenomic and transcriptome profiles and comparing them with surrounding non-malignant tissue (SNT) and normal glans (NG).Results: Genome-wide methylation analysis revealed 171 hypermethylated probes in PeCa. Transcriptome profiling presented 2,883 underexpressed and 1,378 overexpressed genes. Integrative analysis revealed a panel of 54 genes with an inverse correlation between methylation and gene expression levels. Distinct methylome and transcriptome patterns were found for human papillomavirus (HPV)-positive (38.6%) and negative tumors. Interestingly, grade 3 tumors showed a distinct methylation profile when compared to grade 1. In addition, univariate analysis revealed that low BDNF methylation was associated with lymph node metastasis and shorter disease-free survival. CpG hypermethylation and gene underexpression were confirmed for a panel of genes, including TWIST1, RSOP2, SOX3, SOX17, PROM1, OTX2, HOXA3, and MEIS1.Conclusions: A unique methylome signature was found for PeCa compared to SNT, with aberrant DNA methylation appearing to modulate the expression of specific genes. This study describes new pathways with the potential to regulate penile carcinogenesis, including stem cell regulatory pathways and markers associated to a worse prognosis. These findings may be instrumental in the discovery and application of new genetic and epigenetic biomarkers in PeCa.
Keywords: Penile carcinomas; DNA methylome; Human papillomavirus; Molecular marker; Transcriptome